Functional differentiation and adaptive responses of absorptive and transport roots in alpine grassland plants under nitrogen and phosphorus addition - Du, Jinke; Li, Xueqi; Sun, Qiang; Yang, Lu; Li, Ying; Dong, Shikui (Frontiers in Plant Science, 2026)
Fine root functional traits are critical for shaping plant strategies in below-ground resource acquisition and ecosystem functioning. However, previous studies have predominantly focused on fine roots as a whole or overlooked functional differentiation between root order, making it challenging to elucidate the response patterns and driving mechanisms of different root orders under nutrient addition. We conducted this study with controlled nitrogen and phosphorus addition experiments in alpine meadow and steppe ecosystems on the Qinghai-Tibetan Plateau (QTP), systematically analysing the response and differentiation characteristics of two fine root types—absorptive roots and transport roots—in key traits including root diameter (RD), specific root length (SRL), root tissue density (RTD), and root nitrogen concentration (RN). The results indicated that absorptive roots predominantly exhibited a ‘high SRL, low RTD’ absorptive trait combination, whilst transport roots displayed a ‘low SRL, high RTD’ conservative trait profile, these differentiation patterns remained consistent across all nitrogen and phosphorus addition treatments. This functional differentiation remains stable across different nitrogen and phosphorus treatments and grassland types, corroborating the framework of functional specialisation within root functional modules. Within the two-dimensional space, both absorptive and transport roots formed trade-off structures along the ‘SRL–RD’ and ‘RTD–RN’ axes, reflecting the coexistence of dual-axis economic spectra: ‘acquisition–conservation’ and ‘independence–cooperation’. Overall, the alpine grasslands plants on the QTP adapt to cold and nutrient–poor environments by balancing structural and metabolic traits, thereby supporting a strategy of synergistic trait trade-offs for environmental adaptation.